Origin of Boron and Brine Evolution in Saline Springs in the Nangqen Basin, Southern Tibetan Plateau. (2nd July 2018) - Han, Ji-long; Han, Feng-qing; Hussain, Syed-Asim; Liu, Wen-yu; Nian, Xiu-qing; Mao, Qing-fei
Abstract : The Nangqen Basin is a typical shearing-extensional basin situated in the hinterland of the Tibetan Plateau. It contains abundant saline spring resources and abnormal trace element enrichments. The hydrochemical molar ratios (Na/Cl, B/Cl, and Br/Cl), H-O isotopes, and B isotopes of the saline spring were systematically measured to describe the evolution of brines and the origin of the boron. The sodium chloride coefficient of the water samples in this area is around 1.0 or slightly greater, which is characteristic of leached brines; the highest B/Cl value is 4.25 (greater than that of seawater). The Na/Cl, B/Cl, and Br/Cl values of the springs are clear indicators of a crustal origin. Theδ 18 O values of the spring waters range from −12.88‰ to −16.05‰, and theδ D values range from −100.91‰ to −132.98‰ . Meanwhile the B content and B isotopes in the saline springs are in the ranges of 1.00 to 575.56 ppm and +3.55‰ to +29.59‰, respectively. It has been proven that the saline springs in the Nangqen Basin are a type of leached brine, suggesting that the saline springs have a terrestrial origin. Theδ 11 B-B characteristics of the springs are similar to those observed in the Tibetan geothermal area, indicating that these two places have the same B source. Moreover, they have a crustal origin (marine carbonate rocks and volcanic rocks) instead of a deep mantle source.